Specific features of the use of scenario approach in formation of the company’s development strategy Особенности использования сценарного подхода при формировании стратегии развития компании - Omarov Shakhin A. (Problemi Ekonomiki, 2011)
The article considers specific features of scenario approach in formation of the company’s development strategy. The essence of this approach and its advantages when solving problems of strategic planning are analyzed. A comparative characteristic of basic prerequisites of the scenario approach and traditional strategic planning is given. Characteristics of the scenario approach and mechanism of execution of scenario planning are considered. В статье рассматриваются особенности применения сценарного подхода при формировании стратегии развития компании. Проанализирована суть данного подхода и его преимущества при решении проблем стратегического планирования. Приведена сравнительная характеристика базовых предпосылок сценарного подхода и традиционного стратегического планирования. Рассмотрены характеристики сценарного подхода и механизм осуществления сценарного планирования.